(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Coin-operated water dispensing machines are becoming more and more common because of how convenient and simple they are to operate. When a genuine coin is detected, such machines are meant to deliver freshwater or numerous kinds of drinking liquids in accordance with the availability in the machine. Water dispenser are special machines utilized to provide fresh water or other drinks which is good for people. The problem why the study is conducted is to provide knowledge and significances about the water dispenser which correctly organized in coin based which is beneficial in platforms like railway stations, roadways, shopping mall, and similar other places. The study focuses deal with reviewing and determination of coin-based water dispenser system. The findings of this study contribute to key knowledge as well as advancement of this technology by offering insights into the possible uses, constraints, and upcoming advances of coin-based water dispenser systems.